Does it matter who places the intravenous? An inter-professional comparison of prehospital intravenous access difficulties between physicians and paramedics - Prottengeier, Johannes; Maier, Jan-Niklas; Gall, Christine; Heinrich, Sebastian; Schmidt, Joachim; Birkholz, Torsten (European Journal of Emergency Medicine, 2016)
Depending on the specific national emergency medical systems, venous cannulations may be performed by physicians, paramedics or both alike. Difficulties in the establishment of vascular access can lead to delayed treatment and transport. Our study investigates possible inter-professional differences in the difficulties of prehospital venous cannulation.Paramedics were interviewed for their personal attitudes towards and experiences in venous access. We analysed 47 candidate predictor variables in terms of cannulation failure and exceedance of a 2 min time threshold. Multivariable logistic regression models were fitted for variables of potential predictive value (P<0.25) and evaluated by the area under the curve (AUC>0.60) of their respective receiver operating characteristic curve. Results were compared with previously published data from emergency physicians.A total of 552 cannulations were included in our study. All 146 participants voted that paramedics should be eligible to perform venous catheterizations. Despite ample experience in the task, almost half of them considered prehospital venous cannulations more difficult than those performed in hospital. However, the multivariable logistic regression found only patient-related and puncture site factors to be predictive of cannulation failure (patient age, vein palpability with tourniquet, insufficient ambient lighting: model AUC: 0.72) or cannulation delay (vein palpability with tourniquet: model AUC: 0.60).Our study shows that venous cannulation is well established among paramedics. It presents itself with similar difficulties across medical professions. Not the numerous specific circumstances of prehospital emergency care, but universal factors inherent to the task will influence the success at venous catheterization.
EVALuna2:16736

Low amounts of bisecting glycans characterize cerebrospinal fluid-borne IgG - Knopf, Jasmin; Magorivska, Iryna; Maier, Jan-Niklas; Spitzer, Philipp; Bilyy, Rostyslav; Biermann, Mona; Hychka, Kateryna; Bondt, Albert; Wuhrer, Manfred; Toes, Rene E. M.; Schett, Georg; Herrmann, Martin; et al. (Journal of Neuroimmunology, 2018)
Immunoglobulin G (IgG) harbors a conserved N-glycosylation site which is important for its effector functions. Changes in glycosylation of IgG occur in many autoimmune diseases but also in physiological conditions. Therefore, the glycosylation pattern of serum IgG is well characterized. However, limited data is available on the glycosylation pattern of IgG in cerebrospinal fluid (CSF) compared to serum. Here, we report significantly reduced levels of bisected glycans in CSF IgG. Galactosylation and sialylation of IgG4 also differed significantly. Therefore, we propose a common mechanism mediating glycosylation changes of IgG at the transition from serum to CSF in steady state conditions.
EVALuna2:34466

N-truncation and pyroglutaminylation enhances the opsonizing capacity of A?-peptides and facilitates phagocytosis by macrophages and microglia - Condic, Mateja; Oberstein, Timo; Herrmann, Martin; Reimann, Mareike Carola; Kornhuber, Johannes; Maier, Jan-Niklas; Spitzer, Philipp (Brain Behavior and Immunity, 2014)
Abnormal accumulations of amyloid-? (A?)-peptides are one of the pathological hallmarks of Alzheimer's disease (AD). The precursor of the A?-peptides, the amyloid precursor protein (APP), is also found in peripheral blood cells, but its function in these cells remains elusive. We previously observed that mononuclear phagocytes release A?-peptides during activation and phagocytosis, suggesting a physiologic role in inflammatory processes. Here, we show that supplementing the media with soluble N-terminally truncated A?(2-40) and A?(2-42) as well as A?(1-42) induced the phagocytosis of polystyrene particles (PSPs) by primary human monocytes. If the PSPs were pre-incubated with A?-peptides, phagocytosis was induced by all tested A?-peptide species. N-terminally truncated A?(x-42) induced the phagocytosis of PSPs significantly more effectively than did A?(x-40). Similarly, the phagocytosis of Escherichia coli by GM-CSF- and M-CSF-elicited macrophages as well as microglia was particularly facilitated by pre-incubation with N-terminally truncated A?(x-42). The proinflammatory polarization of monocytes was indicated by the reduced MSRI expression and IL-10 secretion after phagocytosis of PSPs coated with A?(1-42), A?(2-42) and A?(3p-42). Polarization of the macrophages by GM-CSF reduced the phagocytic activity, but it did not affect the capabilities of A?-peptides to opsonize prey. Taken together, A?-peptides support phagocytosis as soluble factors and act as opsonins. Differential effects among the A?-peptide variants point to distinct mechanisms of interaction among monocytes/macrophages, prey and A?-peptides. A proinflammatory polarization induced by the phagocytosis of A?-peptide coated particles may provide a model for the chronic inflammatory reaction and sustained plaque deposition in AD.
EVALuna2:13018